Implementation Of Nationalist Character Education in Civic Education at an Islamic Qur’ani Elementary School - Fadhil Nur Hidayat; Aziz Mukhamad Thoha; Dexani Widyasari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2026)
The current of globalization threatens the national identity of the younger generation, yet research on the implementation of national character education at the micro-level of elementary schools remains limited. This study aims to describe the implementation of nationalism character education through Civics Education in the fifth grade of an Islamic Qur'anic elementary school in East Lampung and to examine the process of internalizing nationalist values among students. A qualitative approach utilizing a case study design was employed. Data collection took place from April to May 2026 through observation, in-depth interviews, and documentation. The informants consisted of four individuals, namely the principal, the Civics Education teacher, and two fifth-grade students selected based on the criteria of highest academic and non-academic achievements. Data analysis was conducted using the Miles and Huberman interactive model. The findings indicate that the implementation proceeds contextually and is integrated through teacher role-modeling and the habituation of discipline, responsibility, cooperation, and appreciation of differences. The internalization of values in students is reflected in their active participation and compliance with rules, despite facing challenges regarding time constraints and external environmental influences outside of school. This study offers an empirical model for the implementation of nationalism character based on the interaction of key actors at the elementary school level, and identifies the necessity for school-family synergy and a reflective pedagogical approach.